2018
DOI: 10.1186/s12889-018-5359-z
|View full text |Cite
|
Sign up to set email alerts
|

Health conditions and lifestyle risk factors of adults living in Puerto Rico: a cross-sectional study

Abstract: BackgroundPuerto Rico is experiencing an economic and healthcare crisis, yet there are scarce recent and comprehensive reports on the population’s health profile. We aimed to describe prevalent risk factors and health conditions of adults living in Puerto Rico and assess their interrelationship.MethodsParticipants (n = 380) aged 30-75y recruited from a 2015 convenience sample in primary care clinics in the San Juan, Puerto Rico metropolitan area answered cross-sectional interviewer-administered questionnaires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 33 publications
(42 reference statements)
1
35
0
Order By: Relevance
“…Among women enrolled in the Boston Puerto Rican Health Study, the mean CES-D score was 24.4, which is markedly increased compared to those in PROTECT [20]. Similar high scores on the CES-D (mean score of 21.8) were observed among a convenience sample of women recruited from primary care clinics in San Juan, PR [40]. Among women enrolled in the Pregnancy Study Online, an online-based preconception cohort study of women in the U.S. and Canada, the mean PSS score was 15.8, which is also slightly higher than the mean PSS score in PROTECT [41].…”
Section: Table 4 Crude and Adjusted 1 Odds Ratios Of Preterm Birth (mentioning
confidence: 53%
“…Among women enrolled in the Boston Puerto Rican Health Study, the mean CES-D score was 24.4, which is markedly increased compared to those in PROTECT [20]. Similar high scores on the CES-D (mean score of 21.8) were observed among a convenience sample of women recruited from primary care clinics in San Juan, PR [40]. Among women enrolled in the Pregnancy Study Online, an online-based preconception cohort study of women in the U.S. and Canada, the mean PSS score was 15.8, which is also slightly higher than the mean PSS score in PROTECT [41].…”
Section: Table 4 Crude and Adjusted 1 Odds Ratios Of Preterm Birth (mentioning
confidence: 53%
“…The role of doctors in elevating nutrition was mentioned, and having doctors support and advocate for evidenced-based nutrition practice has been deemed as crucial to achieving the World Health Organization's Decade of Action on Nutrition (53). Primary prevention of chronic disease through a healthy diet may help reduce morbidity in PR, as adults in PR with a self-rated fair/poor diet (vs. excellent/good) had twice the odds of having two or more chronic diseases (vs. > 2) (11).…”
Section: Discussionmentioning
confidence: 99%
“…In PR, 62% of adults reported obtaining health and nutrition information from a non-physician healthcare professional, such as a nutritionist or dietitian, and 78% of those reported trusting this information (11). Thus, residents of PR may trust and benefit from individual and population-based strategies to improve healthy eating recognized by nutrition professionals.…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, the Department of Health of PR published statistics demonstrating a high prevalence of such CHCs as hypertension (39.4%), obesity (30.5%), and diabetes (13.7%) in the local population; these rates indicate that a significant number of people (in PR) are physically vulnerable to disaster. 28,29,57 Regarding mental health, the needsassessment study of mental health and substance-use disorders and service usage in the adult population of PR reported that 23.7% of that population met the criteria for at least 1 diagnosis of a mental health problem (including substance-use disorders). 28,29,57 Most of the patients who requested the support of the THCU did so because they lived in areas that had suffered the long-term loss of electricity or water (usually both); without those critical resources, these patients were unable to satisfy the treatment needs of their pre-existing medical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding individuals in PR who had pre-existing mental health disorders, a needs-assessment study of mental health and substance-use disorders and service usage in this (adult) population, reported that 23.7% met the criteria for at least 1 diagnosis of mental health problems (including substance-use disorders). 28,29 This report provided an estimation of the number of individuals who were most likely to require post-disaster psychological care.…”
Section: Methods the Impact Disastrous Events Have On Mental Healthmentioning
confidence: 99%